Penegakan Hukum Tindak Pidana Illegal Fishing dengan Penenggelaman Kapal dalam Perspektif Pertahanan Nasional Indonesia - Kristanto, Beny (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The sea and all of its resources are part of Indonesia's territory, which must be defended with all efforts in order to defend the state's sovereignty, territorial integrity, and the safety of the entire nation from threats and disturbances to the nation's and state's integrity. The 1945 Constitution mandates that the earth, water, and natural resources contained therein be controlled by the state and used for the greatest prosperity of the people. Because Indonesia has such a large ocean area and a strategic location directly adjacent to other countries, fishing theft by fishermen from neighboring countries is common (illegal fishing). Illegal fishing is a form of threat or disturbance to the sovereignty of Indonesian territory, and those who commit it must face serious consequences. Indonesia, as a state of law, must take firm action against those who engage in illegal fishing, including law enforcement. Law enforcement against illegal fishing is based on Republic of Indonesia Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 Concerning Fisheries, which includes the authority to destroy objects and/or tools used in and/or resulting from illegal fishing. Sinking fishing vessels flying foreign flags is a fishery crime. An empirical legal approach is used in this study. This paper seeks to examine the process of law enforcement for the crime of illegal fishing, all the way up to the sinking of ships used in the crime of illegal fishing, from the standpoint of national defense in Indonesian waters. The sinking of the perpetrator's ship is an effective effort to defend the sovereignty of the Republic of Indonesia by sinking the ship after receiving a judge's decision through the trial process, so that the government has a strong basis to sink the ship.